From confrontation to cooperation - institutional support in building cooperation of Polish enterprises - Joanna Bednarz; Magdalena Markiewicz (Institute of Economic Research (IER), 2015)
The article presents results of critical theoretical and empirical analysis of cooperation between Polish enterprises based on two models: made by T. Ozawa and M.E. Porter, and followed by market research concerning opportunities to support cooperation of Polish enterprises. Polish companies seem to opt for confrontation, as the main market strategy, basing on the development of one company while worsening the position of rivals at the same time. The aim of this paper is to show possibilities in supporting Polish companies to build their capabilities, as well as identifying barriers, in transition from confrontation to cooperation. The article is divided into four parts. In the first part, there are defined the stages of development of economy and enterprises in Europe, concentrating the attention on Poland, with reference to T. Ozawa model. The analysis covers the indicators included in European Innovation Scoreboard, Exploratory Approach to Innovation Scoreboard, Global Summary Innovation Index, and STI indicators, with regard to cooperation aspects. In the second part the authors analyse the essence and forms of cooperation between companies. The third part of the paper concentrates on the market research of the support means available for Polish enterprises. In conclusion, there was given a brief summary of the main findings about opportunities and barriers of institutional approach towards cooperation between Polish enterprises. In the paper two types of research methods were used: methods of data collection and methods of organizing and processing information. There can be enumerated especially methods of systems, cause and logical analysis of institutional support.
Keywords: D21; D85; F63; L14; L21; L53; 330; cooperation; enterprise policy; institutional support; economic development; Polish enterprises